The Shape of Fear : Horror and the Fin de Siècle Culture of Decadence - Navarette, Susan J., 1960- (Book collections on Project MUSE., 1998)
During the last decades of the nineteenth century, Charles Darwin, Thomas Henry Huxley, Walter Pater and others changed the nature of thought concerning the human body and the physical environment that had shaped it. In response, the 1890s saw the publication of a series of remarkable literary works that had their genesis in the intense scientific and aesthetic activity of those preceding decades -- texts that emphasized themes of degeneration and were themselves stylistically decompositive, with language both a surrogate for physical deformity and a source of anxiety. Susan J. Navarette exami.